2017
DOI: 10.1186/s40623-017-0694-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave group velocity in the Osaka sedimentary basin, Japan, estimated using ambient noise cross-correlation functions

Abstract: Inter-station cross-correlation functions estimated using continuous ambient noise or microtremor records were used to extract the seismic wave propagation characteristics of the Osaka sedimentary basin, Japan. Temporary continuous observations were conducted at 15 sites in the Osaka basin between 2011 and 2013. The data were analyzed using seismic interferometry. The target period range was 2-8 s. Cross-correlations between all of the possible station pairs were calculated and stacked to produce a year-long d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the Kanto basin (with an area about 17 000 km2, Koketsu & Kikuchi 2000), where Rayleigh waves are predominant, the shear-wave velocity inside the basin gradually increases with depth (e.g. Takemura et al 2015); however, in the smaller Osaka basin (of elliptical shape and with an area about 3600 km2, Asano et al 2016), where Love waves predominate over Rayleigh waves, a clear unconformity at the sediment-bedrock boundary (between 1 and 1.5 km deep) with a strong impedance contrast in shear-wave velocity is observed at the subsurface (Asano et al 2017). The free surface condition is a sufficient condition for Rayleigh waves to develop, even in homogeneous (or smooth varying) media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Kanto basin (with an area about 17 000 km2, Koketsu & Kikuchi 2000), where Rayleigh waves are predominant, the shear-wave velocity inside the basin gradually increases with depth (e.g. Takemura et al 2015); however, in the smaller Osaka basin (of elliptical shape and with an area about 3600 km2, Asano et al 2016), where Love waves predominate over Rayleigh waves, a clear unconformity at the sediment-bedrock boundary (between 1 and 1.5 km deep) with a strong impedance contrast in shear-wave velocity is observed at the subsurface (Asano et al 2017). The free surface condition is a sufficient condition for Rayleigh waves to develop, even in homogeneous (or smooth varying) media.…”
Section: Discussionmentioning
confidence: 99%
“…To invert the dispersion curves and further suppress the incoherent signals, we average the positive and negative sides of the crosscorrelation functions between 0.1 and 2 Hz to obtain what is called the symmetric signal. This operation has been commonly used in various applications of the cross-correlation technique (Bensen et al 2007;Lin et al 2008;Asano et al 2017;Vassallo et al 2019) in order to better approximate the Green's function between stations pairs. To perform the time-frequency analysis, we focused on the symmetric cross-correlation functions.…”
Section: Rr Rt Rzmentioning
confidence: 99%
“…However, our study area was barely touched, and no other borehole data (in addition to N and soil classification) were available to differentiate the different sand/gravel and clay/silt groups. Asano et al (2017) studied the Osaka sedimentary basin with ambient noise cross-correlation functions. They hinted at a shallower seismic bedrock (200∼800 m) in our study area, which is almost at the edge of their focus area.…”
Section: Priors and Likelihoods Of Site Amplificationsmentioning
confidence: 99%
“…Despite colossal works have been done to build realistic three-dimensional earthquake hazard models, uncertainties naturally remain in the mechanical and geometrical properties of the geological strata due to the intrinsic complexity of the Earth and the difficulty to image it. Past studies have shown that physics-based ground motion predictions below 1 Hz can fairly reproduce the observations (e.g., Komatitsch et al 2004;Iwata et al 2008;Lee et al 2008;Koketsu et al 2009;Asano et al 2016Asano et al , 2017, however, predictions above 1 Hz still need a better understanding of the governing phenomena involved in the source, path and site effects. For instance, Graves & Pitarka (2016) showed that a key factor in matching the observed ground motion characteristics for frequencies larger than 1 Hz is obtaining the proper level of coherence in both the radiation and propagation of the wavefield; and Maufroy et al (2015) pointed out that the differences between the observed and predicted ground motions have multiple origins, like the accuracy of source parameters or the uncertainties in the description of the geological medium.…”
mentioning
confidence: 99%